2014
DOI: 10.1007/s12263-014-0388-4
|View full text |Cite|
|
Sign up to set email alerts
|

The PNPLA3 Ile148Met interacts with overweight and dietary intakes on fasting triglyceride levels

Abstract: The Ile148Met (rs738409, G-allele) in the patatin-like phospholipase domain-containing protein 3 gene (PNPLA3) associates with liver fat content and may lead to loss-of-function (hydrolysis) or gain-of-function (CoA-dependent lysophosphatidic acid acyltransferase) defects. PNPLA3 is up-regulated by dietary carbohydrates, and interactions between rs738409 and carbohydrates, and sugar and ω6:ω3-polyunsaturated fatty acid (PUFA) ratio on hepatic fat accumulation have been reported. We examined interaction between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…Overall, differently tailored diets might be needed in over-and normal-weight individuals to diminish the harmful effects of the PNPLA3 allele. For example, Stojkovic et al [30] postulated that diet, especially sucrose, and overweight modulate the direction of the association between variant PNPLA3 and hepatic steatosis. Several reports showed that obese individuals who carry the PNPLA3 prosteatotic variant develop more severe hepatic phenotypes [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, differently tailored diets might be needed in over-and normal-weight individuals to diminish the harmful effects of the PNPLA3 allele. For example, Stojkovic et al [30] postulated that diet, especially sucrose, and overweight modulate the direction of the association between variant PNPLA3 and hepatic steatosis. Several reports showed that obese individuals who carry the PNPLA3 prosteatotic variant develop more severe hepatic phenotypes [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Since the physiopathology of NAFLD is tightly related to the metabolic syndrome, a link between rs738409[G] and the parameters that define the metabolic syndrome was a likely hypothesis. Indeed, some authors have observed an association between PNPLA3 and insulin resistance [20], and lower fasting triglycerides in severely obese patients and in individuals from Asian descent [21,22]. However, the vast majority of studies have shown that PNPLA3 was not associated with BMI, serum lipid, or glycaemic traits [6,13,23].…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…The PNPLA3 rs738409[G] variation displays a strong interaction with the environment. Indeed, as highlighted above, the increased susceptibility to liver damage observed with rs738409[G] occurs predominantly in the presence of a concomitant liver insult (e.g., obesity, alcohol consumption, viral infection) or in association with increased consumption of certain types of fatty acids [21,102,103]. Although rs738409[G] might not be directly associated with all these risk factors, such as every feature of the metabolic syndrome, these phenotypes may, in fact, trigger the impact of PNPLA3 on steatosis and fibrogenesis and the complex relationships among these factors should not be dissociated.…”
Section: The Contribution Of Pnpla3 To Liver Damage Risk and Its Predmentioning
confidence: 99%
“…The rs738409 variant similarly confers risk for increased histological severity dissociated from its effects on central obesity and IR [157,158] . Its pathogenic role in impaired lipid homeostasis as evidenced by a peripheral decrease in serum triglyceride, total and high-density lipoprotein cholesterol [159,160] is furthermore unmasked in the presence of increased visceral adiposity [161] and impaired glucose tolerance [162] , in addition to being modulated by lifestyle and dietary habits [161,163] . It has further been proposed that lipotoxicity and inflammatory stress resulting from impaired intra-hepatic lipid metabolism and free cholesterol deposition associated with PNPLA3 rs738409 activates dormant hepatic stellate cells (HSCs), leading to increased fibrogenesis.…”
Section: Incorporation Of Personalized Genomic Testing To Existing Comentioning
confidence: 99%